Bridging Two Worlds Comparing Classical Political Thought and Statecraft in India and China - Acharya, Amitav; Bell, Daniel A.; Bhargava, Rajeev; Yan, Xuetong (University of California Press, 2023)
The rise of China and India could be the most important political development of the twenty-first century. What will the foreign policies of China and India look like in the future? What should they look like? And what can each country learn from the other? Bridging Two Worlds gathers a coterie of experts in the field, analyzing profound political thinkers from these ancient regions whose theories of interstate relations set the terms for the debates today. This volume is the first work of its kind and is essential reading for anyone interested in the growth of China and India and what it means for the rest of the world. "This brilliant volume shines a light on the two great civilizations that will once again drive world history. No volume could be more timely, more relevant, and more needed than this one." - KISHORE MAHBUBANI, Distinguished Fellow, Asia Research Institute, NUS, and author of The Asian 21st Century "With the recently elevated economic and political power of China and the great potential of India in the twenty-first century, interdisciplinary dialogue and engagement such as is found in this book is necessary for contemporary debates in political theory and international relations." - KUIYI SHEN, Professor of Asian Art History, Theory, and Criticism, University of California, San Diego"